'How many' and 'how much' dissociate in the parietal lobe. - Lecce, Francesca; Walsh, Vincent; Didino, Daniele; Cappelletti, Marinella (Cortex: A Journal Devoted to the Study of the Nervous System & Behavior, 2015)
We investigated whether two features that are fundamental for quantity processing, namely numerosity and continuous quantity - or 'how many' versus 'how much' - may dissociate in the parietal lobe. Fourteen mathematically-normal participants performed a well-established numerosity discrimination task after receiving continuous theta burst transcranial magnetic stimulation (TBS) over the left or right intraparietal sulcus (IPS) or the Vertex. We performed a detailed analysis of accuracy (based on the Weber Fraction, wf), which distinguished between trials in which numerosity was anti-correlated or 'incongruent' to other continuous measures of quantity, and trials in which numerosity and other continuous features were 'congruent'. Congruent trials can be processed by integrating numerosity or continuous quantity features like cumulative area since they correlate. Instead incongruent trials can only be processed based on numerosity and requires inhibiting cumulative area or other continuous quantity features like dot size and would lead to incorrect judgment if these features are used as a proxy for numerosity. We found an increase of wf, i.e., weakened numerosity processing in incongruent but not congruent trials following left IPS-TBS, which suggests that numerosity processing was impaired while continuous quantity processing remained unchanged. Moreover, wf increased in congruent but not in incongruent trials following right IPS stimulation. We concluded that left and right parietal are respectively critical for numerosity discrimination, i.e., 'how many' or alternatively for response selection, and for integrating numerosity and continuous quantity features.